The simplified Chinese version of the Knee Injury and Osteoarthritis Outcomes Score (KOOS) in individuals with knee osteoarthritis for mainland China: the study of reliability and validity - Liying Yang; Jatuporn Suttiwong; Yanfen Fu; Komsak Sinsurin (SpringerOpen, 2023)
Abstract Background The Knee Injury and Osteoarthritis Outcomes Score (KOOS) is a free clinical tool commonly used to evaluate the symptoms and functional status of patients with knee injury. For people who speak Chinese, the Hong Kong Chinese and Singapore Chinese versions are preferred. However, variations in the Chinese language and culture are influenced by the country's geography. KOOS for Mainland China has not been reported. Therefore, the current study was to cross-culturally translate the original English version into a simplified Chinese version and to investigate its psychometric properties. Methods The simplified Chinese KOOS was obtained through forward-backward translation according to appropriate guidelines. A total of 158 individuals with knee osteoarthritis (KOA) were recruited from 13 hospitals in China to examine the psychometric properties. The test-retest questionnaire was performed at an interval of 5-7 days. Test-retest reliability and internal consistency were evaluated using the intraclass correlation coefficient (ICC) and Cronbach's alpha, respectively. The data of the first test were used to analyse the construct validity of the simplified Chinese KOOS and Chinese SF-36 through convergent and discriminant validity using Spearman's correlation coefficient. Results Cross-cultural translation exhibited minor cultural differences, and the questionnaire was well understood by the patients. The data from 128 patients, used for the test-retest reliability study, showed good to excellent reliability, with an ICC of 0.808-0.976 for all KOOS subscales. The Cronbach's alpha for all subscales ranged from 0.757 to 0.970, indicating acceptable internal consistency. There was a low-to-high correlation between the five domains of the simplified Chinese version of the KOOS and all domains of the SF-36 in construct validity. Conclusion The simplified Chinese KOOS demonstrated acceptable reliability and validity. In clinical practice and research, this version can help provide valuable information on health-related quality of life for Chinese individuals with KOA in mainland China.